A Psycholinguistic Study of Language Difficulties in Patients with Broca's Aphasia and Potential Treatments - Selviya Yuliana; Handani Handani; Selmia Selmia; Irmawati Irmawati; Yusri Yusri (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. Afasia Broca is a talking function disorder caused by a brain abnormality in the broca area. Most Afasians find their lives different at all. Things that were before can be done easily, now done with hardship and took more time. Many Afasian sufferers don't believe in themselves and worry about his future. This research aims to describe the difficulty of the language experienced by the Afasian Broca and her handling. The method used is a quality that is a systematic description, factual, and accurate of fact. The data collection technique used in this research is observation, interviews and documentation. The data analysis technique applied by researchers is a data reduction and data presentation after that withdrawal conclusion. Research results indicate that the difficulty of speaking the language experienced by the suffering of Afasia Broca, is difficult to form a complete sentence, speaking to irregular rhythm, often stopping when talking, trouble writing, ability to read a long line, gramatic language, hardly to start talking, often say unrecognized language, often utter unrecognizable words. The handling of the Afasian sufferers depends on the risk factor experiencing Afasian suffering